Effect of Biofertilizer and Spraying Phenylalanine on Mineral Content and Antioxidant Compounds of Dill - Thamena Farhan Kadhom Sachet; Maher H. S. Al-Mohammad; Jamal Ahmed Abbass (Indian Journal of Forensic Medicine & Toxicology, 2021)
The field experiment was carried out in a private field in Babil Governorate, Abi Ghark district, for the winterseasons 2018-2019 and 2019-2020 to study the effect of biological fertilizer and phenylalanine spraying onthe content of the shoots and seeds of oil and some active compounds. The treatments were distributed in aglobal experiment according to a randomized complete block design (RCBD) with three replications. Theexperiment included two factors, the first is the bacterial vaccine Azotobacter chroococcum with two levels(inoculum and without inoculation) and the second is spraying with the amino acid Phenylalanine in threeconcentrations 0, 75 and 150 ml-1. The averages were compared according to the LSD test at a probabilitylevel of 0.05. The results showed that the treatment of biological fertilizer and spraying with the amino acidPhenylalanine was significantly superior in all the studied traits, which included the oil yield (gm.plant-1),the percentage of nitrogen, phosphorus and potassium and the shoots content of total phenols (mg.kg-1) andtotal flavonoids (mg.kg-1) and total flavonoids (mg. . Kg-1), percentage of free radical suppression and totalantioxidant capacity (mg. 100 g-1). The best results were when the two-way treatment (bio-fertilizer×150ml.1-Phenylalanine), which gave the highest oil yield of 0.677 and 0.907 g. Plant-1, for the two seasonsrespectively, compared with the comparison treatment that gave the lowest yield for both seasons of theexperiment.